Testicular function after combination chemotherapy in childhood for acute lymphoblastic leukaemia. Issue 4 (April 1981) - Shalet, S M; Hann, I M; Lendon, M; Morris Jones, P H; Beardwell, C G
Abstract : We have assessed testicular function with luteinising hormone-releasing hormone (LH-RH) and human chorionic gonadotrophin stimulation tests in 44 boys previously treated with, or currently receiving, chemotherapy for acute lymphoblastic leukaemia (ALL). At the same time a testicular biopsy was performed in each boy and the morphology was studied. Histologically the chemotherapy appeared to damage the tubular system in particular, and the degree of damage was assessed by estimating the tubular fertility (TF) index which is defined as the percentage of seminiferous tubules containing identifiable spermatogonia. The mean TF index in all 44 biopsies was 51%. Only 2 of the 44 boys showed an absent or blunted testosterone response to human chorionic gonadotrophin. This suggests that Leydig cell function is rarely impaired by such chemotherapy and that most of the boys, similarly treat for ALL, will undergo normal pubertal maturation. Apart from the basal luteinising hormone (LH) levels in the prepubertal group which could not be compared, the median basal serum follicle-stimulating hormone (FSH), LH, and testosterone concentrations, the median peak FSH and LH responses to LH-RH, and the mean plasma testosterone responses to human chorionic gonadotrophin stimulation did not differ between the prepubertal, early pubertal, and late pubertal groups compared with normal boys of similar pubertal maturation. Three of 32 prepubertal ALL boys, and 5 of 12 pubertal ALL boys showed abnormalities of gonadotrophin secretion. The increased frequency of abnormalities of FSH secretion in the pubertal ALL boys compared with the prepubertal ALL boys could not be explained by more severe tubular damage in the former group. We conclude that moderately severe damage to the tubular system of the testis unassociated with Leydig cell impairment may not be detected in the prepubertal boy with current tests of testicular function.